Association of Intended Route of Delivery and Maternal Morbidity in Twin Pregnancy. Issue 2 (February 2017) - Easter, Sarah Rae; Robinson, Julian N.; Lieberman, Ellice; Carusi, Daniela
Abstract : OBJECTIVE: To evaluate maternal morbidity in twin pregnancies according to intended mode of delivery. METHODS: We assembled a 7-year retrospective cohort (2007–2014) of women delivering viable, vertex-presenting twins at or beyond 32 weeks of gestation without contraindication to labor or uterine scar. We classified women as undergoing a trial of labor to attempt vaginal birth or choosing an elective cesarean delivery. Our primary outcome was a measure of composite maternal morbidity including death, postpartum hemorrhage, infection, major procedure, readmission for infection or reoperation, need for dilation and evacuation for hemorrhage or infection, venous thromboembolism, small bowel obstruction or ileus, or intensive care unit admission. Postpartum hemorrhage was defined as estimated blood loss greater than or equal to 1, 500 mL or need for transfusion. The rate of lacerations in each group was also determined. Using logistic regression to control for confounders, we examined the odds of maternal morbidity according to intended mode of delivery. RESULTS: Of 2, 272 twin pregnancies at or beyond 32 weeks of gestation, 1, 140 (50%) met inclusion criteria with 571 (50%) electing cesarean delivery and 569 (50%) undergoing a trial of labor to attempt vaginal birth. Vaginal delivery of both twins was achieved in 74% (n=418) of women choosing a trial of labor. The rate of maternal morbidity was 12.3% in the trial of labor group compared with 9.1% in the elective cesarean delivery group ( P =.08, adjusted odds ratio [OR] 1.6, 95% confidence interval [CI] 1.1–2.4). Postpartum hemorrhage was more common among women who attempted vaginal delivery (n=52) compared with those electing cesarean delivery (n=28) with rates of 9.1% compared with 4.9%, respectively ( P <.01, adjusted OR 2.2, 95% CI 1.4–3.6) and was responsible for the difference in the composite morbidity rate between groups. CONCLUSION: When adjustment is made for potential confounders, women undergoing a trial of labor with twins experience a higher odds of maternal morbidity than those electing cesarean delivery, primarily as a result of hemorrhage. In pragmatic terms, the tradeoff for a 74% chance of vaginal delivery is a 4% absolute increase in the rate of serious postpartum hemorrhage. Abstract : Women attempting vaginal birth of twins were successful in 74% of cases but experienced higher maternal morbidity, primarily as a result of postpartum hemorrhage.